Anais Do Seminário De Laminação E Conformação 2017
DOI: 10.5151/1983-4764-27735
|View full text |Cite
|
Sign up to set email alerts
|

Study of Grain Boundary Oxidation of High Alloyed Carbon Steels at Coiling Temperature

Abstract: The effect of coiling temperature on selective oxidation behaviour of binary and ternary iron-based model alloys containing different contents of Si or Mn were investigated by SEM and SIMS. The experiments were carried out with a temperature ranging from 450 °C to 700 °C, under N2-5%H2 gas flow with a Dew Point of -3.3°C, for different durations. SEM images of binary iron-based model alloys revealed a decrease of grain boundary oxidation depth with increasing Silicon or Manganese content. At 530°C and 600°C SI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
1
3
0
1
Order By: Relevance
“…Despite slight differences in Cr concentration (0.8 wt.% in [55]) and hydrogen pressure (25 mbar in [55]), the ratio between GB tail penetration and bulk IOZ width, X IG /X IOZ , found in [55] is 2.6 which is in excellent accord with the value 2.9 obtained in the present study. The X IG /X IOZ , ratio is expected to increase with decreasing temperature [56]. While these data independently confirm the enhanced intergranular attack in H 2 /H 2 O for diluted Fe-Cr alloys observed in the present study, the role of alloy chemistry, grain size and especially that of humidity remains obscure.…”
Section: Intergranular Oxidation Attacksupporting
confidence: 81%
See 1 more Smart Citation
“…Despite slight differences in Cr concentration (0.8 wt.% in [55]) and hydrogen pressure (25 mbar in [55]), the ratio between GB tail penetration and bulk IOZ width, X IG /X IOZ , found in [55] is 2.6 which is in excellent accord with the value 2.9 obtained in the present study. The X IG /X IOZ , ratio is expected to increase with decreasing temperature [56]. While these data independently confirm the enhanced intergranular attack in H 2 /H 2 O for diluted Fe-Cr alloys observed in the present study, the role of alloy chemistry, grain size and especially that of humidity remains obscure.…”
Section: Intergranular Oxidation Attacksupporting
confidence: 81%
“…3a, 5a). GB tails or intergranular internal oxidation has been previously reported by Auinger et al [54,55] and Ronqueti et al [56] for diluted (0.2-1 wt.%) binary Fe-Cr, Fe-Al, Fe-Si and Fe-Mn alloys exposed in humidified Ar-H 2 or N 2 -H 2 gas mixtures below FeO formation at 600-700 °C. Intergranular tails were found in Fe-Cr and Fe-Si but not in Fe-Al and Fe-Mn [54,55], while the pattern became more complex in ternary model alloys.…”
Section: Intergranular Oxidation Attackmentioning
confidence: 55%
“…The estimated activation energy for this reaction is close to 280 kJ/mol [11,12]. A recent study carried out on Fe-0.5 % Si, showed that the O diffusion coefficient along GBs, determined using Wagner's theory, could be 60-70 times higher than through the bulk [13]. In this latter study, the intergranular oxidation kinetics was supposed to be controlled only by the diffusion of O through the GBs.…”
Section: Review Of Intergranular Oxidation Of Alloy Ni-base Alloysmentioning
confidence: 74%
“…They also suggested that a larger compressive stress due to more Fe2SiO4 in steels with a higher Si content. This resulted in a deeper penetration layer [70,[85][86][87][88].…”
Section: Oxide Layer Propertiesmentioning
confidence: 99%